Séquence ERC : comment améliorer l’utilisation des méthodes de dimensionnement de la compensation écologique ? - Agnès Mechin; Sylvain Pioch (VertigO)
Insufficient knowledge, tools and shared methodologies are identified as one of the causes of the weakness of the application in France of the mitigation hierarchy. This includes methods to evaluate the achievement of the No Net Loss Goal (MNNL). This article focuses on the issue of operationality from the point of view of the users of the methods (land developers, consultancy and regulators). We analyze the operational dimension of these methods by relying on the theoretical framework defined by ergonomics. We propose a definition of operationality based on three components that are utility, usability and social acceptability. We associate with these three components fifteen criteria chosen from the bibliography and our observations of the stakeholders. The first result of this work shows that about half of the criteria determining a good consideration of the operational dimension of the MAPN are not considered by the designers. At this stage, it can be useful to guide the design, to have a common vocabulary and not to neglect points not taken into account or "forgotten" until then for the MAPN in France.